Interactive Learning Tools for Electrical Engineering and Electronics Course - Antonovičs, U.; Priednieks, Ē. (Elektronika ir Elektrotechnika, 2006)
The article describes a complex of interactive learning tools (more than 20 computer programs for Windows environment – executable files with suplementary help files) in CD-form for "Electrical Engineering and Electronics" course. The programs were developed in Riga Technical University. Now the CD-ROM is transposed from Latvian language into Dutch, English, Estonian, Italian, and Lithuanian languages. A further development of the program complex is discussed. Figures show screen copies of running programs. Ill. 3, bibl. 3 (in English, summaries in English, Russian, Lithuanian).